2018
DOI: 10.1002/nau.23566
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of mirabegron for the treatment of neurogenic detrusor overactivity—Prospective, randomized, double‐blind, placebo‐controlled study

Abstract: Mirabegron (50 mg) improved both urodynamic variables and patient-reported outcomes in patients with NDO. The treatment was tolerated well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 26 publications
2
70
2
Order By: Relevance
“…The bladder compliance improved (increased nearly 10‐fold) and, overall, 88.2% of the patients responded. This is in contrast with findings in NDO patients, where the peak detrusor pressure did not reduce significantly and an improvement in compliance was not universally seen 11,12 . Also, the magnitude of improvement in patients who were on CIC for >6 months (already on CIC group) and those were started on CIC at inclusion in the study was similar.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The bladder compliance improved (increased nearly 10‐fold) and, overall, 88.2% of the patients responded. This is in contrast with findings in NDO patients, where the peak detrusor pressure did not reduce significantly and an improvement in compliance was not universally seen 11,12 . Also, the magnitude of improvement in patients who were on CIC for >6 months (already on CIC group) and those were started on CIC at inclusion in the study was similar.…”
Section: Discussioncontrasting
confidence: 82%
“…In a randomized, double blind, placebo‐controlled study evaluating the role of mirabegron in NDO resulting from SCI or multiple sclerosis, Krhut et al. reported on 66 patients, and concluded that the volume at first detrusor contraction and the bladder compliance significantly improved in the mirabegron group, whereas the increase in cystometric capacity and change in maximum detrusor pressure did not reach statistical significance 11 …”
Section: Discussionmentioning
confidence: 99%
“…However, most relevant to our study is a recent published trial that similarly examined mirabegron in patients with SCI and MS. Krhut et al randomized 66 Czechoslovakian patients with NDO due to MS or SCI to mirabegron or placebo. They found improvements in MMC, volume of first NDO, compliance, pad weights, and several patient‐reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…8 There is interest in using mirabegron for patients with NLUTD due to the potentially better safety and tolerability profile 5,9 ; however, there is limited evidence of its efficacy in this population. 10,11 There are potentially serious consequences of inadequately treated neurogenic bladder parameters; one study found that almost 20% of SCI patients required surgical invention for adverse urodynamic parameters over a 5-year period. 12 In some cases, bladder dysfunction can cause renal dysfunction (estimated at 5% after SCI, and uncommon among MS patients).…”
mentioning
confidence: 99%
“…The β3‐adrenoceptor is involved in detrusor relaxation during the storage phase. The efficacy and safety of a β3‐adrenoceptor agonist (mirabegron) were evaluated in two small RCTs in SCI patients, and showed positive results without safety concerns . In Japan, a β3‐adrenoceptor agonist is approved only for treatment of OAB.…”
Section: Summary Of the Guidelinesmentioning
confidence: 99%